The cellar - Preston, Natasha (Naperville, Illinois : Sourcebooks Fire, 2014)
For months, Summer is trapped in a cellar with the man who took her and three other girls: Rose, Poppy, and Violet.
HL 570
Accelerated Reader AR
Keywords: Kidnapping -- Fiction